Discounting Behavior in Problem Gambling - Patrick Ring; Catharina C. Probst; Levent Neyse; Stephan Wolff; Christian Kaernbach; Thilo van Eimeren; Ulrich Schmidt (Journal of Gambling Studies, 2022)
Problem gamblers discount delayed rewards more rapidly than do non-gambling controls. Understanding this impulsivity is important for developing treatment options. In this article, we seek to make two contributions: First, we ask which of the currently debated economic models of intertemporal choice (exponential versus hyperbolic versus quasi-hyperbolic) provides the best description of gamblers' discounting behavior. Second, we ask how problem gamblers differ from habitual gamblers and non-gambling controls within the most favored parametrization. Our analysis reveals that the quasi-hyperbolic discounting model is strongly favored over the other two parametrizations. Within the quasi-hyperbolic discounting model, problem gamblers have both a significantly stronger present bias and a smaller long-run discount factor, which suggests that gamblers' impulsivity has two distinct sources.
Keywords: 330; time preferences; discounting; risk; incentives; gambling